2006
DOI: 10.1128/iai.00412-06
|View full text |Cite
|
Sign up to set email alerts
|

The BarA-UvrY Two-Component System Regulates Virulence in Avian Pathogenic Escherichia coli O78:K80:H9

Abstract: The BarA-UvrY two-component system (TCS) in Escherichia coli is known to regulate a number of phenotypic traits. Both in vitro and in vivo assays, including the chicken embryo lethality assay, showed that this TCS regulates virulence in avian pathogenic E. coli (APEC) serotype O78:K80:H9. A number of virulence determinants, such as the abilities to adhere, invade, persist within tissues, survive within macrophages, and resist bactericidal effects of serum complement, were compromised in mutants lacking either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 62 publications
1
55
0
Order By: Relevance
“…Over 32 TCSs have been found in nonpathogenic E. coli that are also found in pathogenic E. coli (45). Several TCSs have been associated with the virulence of pathogenic E. coli, and a previous study demonstrated that the TCS BarA/UvrY contributes to APEC pathogenesis (24). Our microarray data showed that several target genes of TCS PhoP/PhoQ were significantly upregulated during APEC O1's growth in serum.…”
Section: Discussionmentioning
confidence: 55%
“…Over 32 TCSs have been found in nonpathogenic E. coli that are also found in pathogenic E. coli (45). Several TCSs have been associated with the virulence of pathogenic E. coli, and a previous study demonstrated that the TCS BarA/UvrY contributes to APEC pathogenesis (24). Our microarray data showed that several target genes of TCS PhoP/PhoQ were significantly upregulated during APEC O1's growth in serum.…”
Section: Discussionmentioning
confidence: 55%
“…It well known that expression of bacterial virulence is regulated by conserved global systems that sense and adapt to changes in the environment. One such well-recognized system is the BarAUvrY two-component system, which has been shown to regulate APEC virulence by down-regulating type 1 and Pap fimbriae, by increasing susceptibility to oxidative stress and by reducing the amount of surface polysaccharide (Herren et al, 2006). In addition, a specific phosphate transport system (Pts) has also been linked with virulence in APEC x7122 strain (Lamarche et al, 2005).…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…VarS/VarA homologues are found in other bacteria, including BarA/UvrY in Escherichia coli and GacS/GacA in Pseudomonas species, and these signalling systems are often involved in virulence in these other bacteria as well (Heeb & Haas, 2001;Herren et al, 2006;Pernestig et al, 2001;Tomenius et al, 2006). The signals that activate VarS/VarA-type systems have not yet been definitively established.…”
Section: Introductionmentioning
confidence: 99%